2015
DOI: 10.1590/0104-1169.0044.2557
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors and mental work load: a reality perceived by nurses in intensive care units

Abstract: OBJECTIVE: To analyse the perception of psychosocial factors and mental workload of nurses who work in intensive care units. It is hypothesised that nurses in these units could perceive psychosocial risks, manifesting in a high mental work load. The psychosocial dimension related to the position's cognitive demands is hypothesised to mostly explain mental work load. METHOD: Quantitative study, with a descriptive, cross-sectional, and comparative design. A total of 91% of the intensive care unit populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 15 publications
4
34
0
21
Order By: Relevance
“…The vision provided by the participants is also consistent with what the literature reports regarding the dark side of the characteristics and tendencies of working conditions in general, both for their psychosocial risk factors 16 - 18 and because of the lack of wellbeing in health care work 5 - 7 , 10 - 12 , 26 - 27 , 30 - 31 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The vision provided by the participants is also consistent with what the literature reports regarding the dark side of the characteristics and tendencies of working conditions in general, both for their psychosocial risk factors 16 - 18 and because of the lack of wellbeing in health care work 5 - 7 , 10 - 12 , 26 - 27 , 30 - 31 .…”
Section: Discussionsupporting
confidence: 86%
“…The role of moderating variables in some of these effects, such as control of process and work content, horizontal and vertical social support, degree of adjustment between demands and labor resources, and the work-family balance or emotional load, has also been studied 12 - 15 . Some research reports the economic and human cost of the lack of prevention of psychosocial risks in work in general and particularly in health care services 16 - 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies also identified that nurses perceived harmful levels of psychosocial factors in the work environment, among which were lack of defined roles, lack of autonomy and little social and instrumental support from colleagues and superiors 4 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…O ritmo de trabalho dos trabalhadores de enfermagem também é destaque nas produções científicas (19,31,33,37) , assim como a carga horária excessiva de trabalho exercida pelos trabalhadores (15,17,19,(27)(28)32,34,39,(42)(43) , dimensionamento inadequado (55)(56) , dificuldade nas relações interpessoais (55) , e estes são considerados fatores determinantes da carga psíquica.…”
Section: Categoria 2 -Condições De Trabalho Que Predispõem àS Cargas unclassified
“…Outras consequências estão voltadas ao desgaste emocional (11,16,23,27,33,36,39,49) , associado à ocorrência de acidentes e problemas de saúde (11) , preocupação, perda de sono, ansiedade, medo, descontrole emocional, problemas no relacionamento com a família (24) , desgaste físico e emocional (27,29,56) . A falha de memória, dificuldade de concentração, medo de cometer erros (13) , e perturbações do sono (13,(37)(38) também são influências das cargas de trabalho na saúde do trabalhador.…”
Section: Categoria 3 -Influências Das Cargas De Trabalho Na Saúde Do unclassified